SUPPLEMENTARY FEEDING ON THE NUTRIENT BALANCE OF LACTATING DAIRY COW AT CONTRASTING TEMPERATURE REGIMES: ASSESSMENT USING CORNELL NET CARBOHYDRATE AND PROTEIN SYSTEM (CNCPS) MODEL - Jayanegara, A.; Sofyan, A. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
Dairy cows often do not receive adequate nutrient supply during their lactation period. This condition caneven be worse if the environmental temperature is not in comfortable range which may occur especially intropical regions. The present research was aimed to simulate the effect of supplementary feeding on nutrientbalance of lactating dairy cow at contrasting temperature regimes using Cornell Net Carbohydrate andProtein System (CNCPS) model. Treatments consisted of feeds (R1: Pennisetum purpureum, R2: P.purpureum + concentrate (60:40), R3: P. purpureum + Gliricidia sepium + Leucaena leucocephala(60:20:20), R4: P. purpureum + concentrate + G. sepium + L. leucocephala (60:20:10:10)) and environmentaltemperatures (T1: 20 oC, T2: 30 oC). The dairy cow inputs in CNCPS were Holstein breed, body weight of500 kg, feed intake of 15 kg (dry matter basis) per day and produced milk 15 kg/day. Based on the CNCPSmodel, there were negative balances of metabolisable energy (ME) and metabolisable protein (MP) if alactating dairy cow fed only by P. purpureum. The ME balance was worse at higher temperature, while theMP balance was remain unchanged. Addition of concentrate mixture (R2) fulfilled the ME and MPrequirements as well as other nutrients. Addition of leguminous tree leaves (R3 and R4) improved thenutritional status of the lactating cow model compared to R1, but did not better than R2. It was concludedthat supplementary feeding is necessary for improving the nutrient balance of lactating dairy cow, especiallywhen the cow is maintained under uncomfortable environmental temperature.